Tari Balanse Madam “Faktor-faktor Yang Mempengaruhi Eksisnya Tari Balanse Madam Di Seberang Palinggam” - Dwi Witri Anggraini; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2020)
This study aims to express the factors that influence the existence of Madam balanse dance at Seberang Palinggam. Type of this research was a qualitative study with using descriptive method. The main instrument of this study was the researcher. The additional instruments used were such as stationery, camera and flash disk. Techniques of data collection werecarried out by using literature study, observation, interviews, documentation. The steps in analyzing data were data collection, reduction, data presentation and drawing conclusions of the research. The results show that the dance originated from trading activity which led to cultural encounters, namely Portuguese culture (dance) with Nias culture (maena). The cultural meeting creates a form of art performance namely Madam Balance Dance. The existence of the Madam balanse dance is influenced by several factors such as: customs, religion, community and government environment. This dance has changed its function from dance as a custom to dance as entertainment, this is because of the lack of interest in the community and the government of Padang to preserve and learn the Madam Balanse dance. One of the efforts to keep the Madam Balanse dance alive and sustainable is that the government have to promote or introduce the Madam Balanse dance again to the public.